Freshwater ecosystem naturalness index: a case study in the upper Limay River Basin, Patagonian Argentina - Magalí Rechencq; María Valeria Fernández; Daniela Milano; Alejandro Sosnovsky; Marcelo Fabián Alonso; Patricio Jorge Macchi (Journal for Nature Conservation, 2026)

Technological variability and raw material procurement in the Cantabrian Lower Magdalenian: Level G1 at El Cierro Cave (Ribadesella, Asturias, Spain) - Diego Herrero-Alonso; Sergio Martín-Jarque; Antonio Tarriño; David Álvarez-Alonso; Selina Delgado-Raack; Alejandro Prieto; Jesús F. Jordá Pardo; Esteban Álvarez-Fernández (Archaeological and Anthropological Sciences, 2026)
This paper presents a comprehensive analysis of the lithic assemblage from Level G1 of El Cierro Cave (northern Spain), attributed to the Cantabrian Lower Magdalenian. The study comprises 2,829 items, including 2,800 knapped artefacts, six macrolithic tools and 23 unmodified pebbles. Lithic procurement is dominated by flint, followed by quartzite and minor amounts of quartz. Eleven flint types have been identified, with local raw materials prevailing, while regional and tracer groups occur in lower proportions, indicating selective long-distance connections within the Basque-Cantabrian Basin. Technological analysis reveals complete operational chains for flake production using locally available resources, alongside greater variability in laminar reduction strategies. Blade production is limited and clearly subordinate to flake-oriented technologies. The retouched tool assemblage, dominated by endscrapers, conforms to typical Upper Palaeolithic techno-typological patterns, whereas backed bladelets are poorly represented. Use-wear analysis indicates a range of activities involving macrolithic tools, potentially linked to both lithic production and the processing of organic materials. Overall, the Level G1 assemblage at El Cierro is characterised by a strong reliance on local raw materials, restricted circulation of distant flints and low investment in laminar production, reflecting procurement strategies operating primarily at a local scale and a technological organisation adapted to domestic activities and reduced mobility.

Petrogenesis of garnet-bearing two-mica leucogranites from the late Paleozoic Deuco pluton, Nahuelbuta Batholith, south-central Chile - Osvaldo Rabbia; Laura Hernández; André Steenken; Eugenio Aragón; Alejandro Demichelis; Alonso Hidalgo (Journal of South American Earth Sciences, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

The use of remote sensing to detect illegal, unreported, and unregulated (IUU) tuna fishing activities in the Peruvian Exclusive Economic Zone - Eizo Muñoz-Sovero; Ramzy Kahhat; Alejandro Deville; Diana Ita-Nagy; David Gonzales; Alonso Montero; Ian Vázquez-Rowe (Marine Policy, 2026)

Spatial distribution and seasonal dynamics of blue shark (Prionace glauca) and shortfin mako (Isurus oxyrinchus) catches from the Spanish surface longline fleet in the North Atlantic - José Carlos Báez; Alejandro Alegría; Julissa de la Rosa; Francisca Salmerón; Patricia Romero-Fernández; Davinia Torreblanca; María Lourdes Ramos-Alonso; José Francisco Moreno; David Macías (Regional Studies in Marine Science, 2026)

Signal of phenotypic plasticity in the population dynamics of the crab Microcassiope xantusii across Pocillopora-dominated coral reefs - Sandra Rodriguez-Huezo; Manuel Ayon-Parente; Arizbeth Alonso-Dominguez; Fabian Alejandro Rodriguez-Zaragoza; Ignacio Caceres (Hydrobiologia, 2026)

Nanoemulsion-based colistin for pulmonary delivery: Enhanced antibacterial efficacy against Acinetobacter baumannii - Marta Martínez-Guitián; Lucía Sanjurjo; Juan Carlos Vázquez-Ucha; Andrea Muras; Alejandro Beceiro; José Crecente-Campo; María José Alonso (Drug Delivery and Translational Research, 2026)

Groundwater origin and circulation within a karst watershed recharge zone: the case of the Upper Guayalejo-Tamesí River Basin, southern Tamaulipas, Mexico - Luis Gerardo Vázquez-Guevara; René Ventura-Houle; Tomás Alejandro Peña-Alonso; Oscar Guevara-Mansilla; Glenda Nelly Requena-Lara; Elizabeth del Carmen Andrade-Limas; Bárbara Azucena Macías-Hernández (Journal of South American Earth Sciences, 2026)

Towards a harmonized database of indoor air contaminant concentrations: Methods and application to CO2 - Gabriel Rojas; Reto Stauffer; Núria Casquero-Modrego; Marcel Loomans; Marc Abadie; Ibrahim Alhindawi; Francesco Babich; Gabriel Bekö; Marie Coggins; Bart Cremers; Bernhard Damberger; Timm Freundorfer; et al. (Building and Environment, 2026)

BiVO₄-assisted photocatalytic ozonation for efficient cyanide degradation in synthetic silver post-leaching effluents - Johan Andrés Vargas Rueda; Alejandro Rafael Alonso Gómez; Rosa María Luna Sánchez; Ricardo López Medina; José Ortiz Landeros; Román Cabrera Sierra; Jorge Vazquez Arenas (Environmental Science and Pollution Research, 2026)
Cyanide is extensively used in hydrometallurgical leaching due to its strong metal-chelating ability, yet its acute toxicity raises major environmental concerns. This study evaluates photoactivated BiVO₄ synthesized by the sol–gel method and combined with ozone for the degradation of metal–cyanide complexes in alkaline matrices (pH 10.5) containing silver, copper, iron, lead, and zinc, representative of effluents from silver leaching in the Mexican mining industry. Synthetic solutions were prepared and characterized to reproduce these conditions. Thermodynamic stability diagrams indicated that free cyanide and complexes such as Ag(CN)₂⁻, Cu(CN)₃ 2 ⁻, and Fe(CN)₆ 4 ⁻ persist at alkaline pH, while lead and zinc showed no tendency to form stable cyanide complexes. Oxidative treatments favored complex dissociation, with cyanate predicted as the main by-product; experimentally, ammonium was identified as the dominant degradation product. The BiVO₄/ozone system under irradiation demonstrated superior performance compared to individual processes, achieving faster cyanide abatement and improved efficiency. Kinetics followed a modified Langmuir–Hinshelwood model that accounted for both surface-mediated photocatalysis and bulk-phase ozone reactions. Complete cyanide removal was achieved in two consecutive cycles, though partial deactivation occurred in the third cycle due to BiVO₄ surface poisoning by adsorbed metals, confirmed by SEM/EDS and atomic absorption. Despite gradual loss of activity, the coupled process consistently removed both free and complexed cyanide while reducing ozone demand compared with conventional ozonation. These findings highlight photocatalytic ozonation with BiVO₄ as a promising and sustainable strategy for the treatment of metallurgical effluents, offering efficient pollutant degradation and lower oxidant consumption in comparison with conventional approaches. Graphical Abstract

Differentiation to insulin-positive cells from human amnion epithelial cells using a pancreatic development mimicry protocol - Daniel Martínez-Rodríguez; Jonathan Salazar-Alonso; Axel Castro-Abrego; Daniela Ávila-González; Omar Martínez-Alarcón; Anayansi Molina-Hernández; Alejandro Martínez-Juárez; Héctor Salvador Godoy-Morales; Diana Elizabeth Lara-Barragán; Wendy Portillo; Nestor Emmanuel Díaz-Martínez; Guadalupe García-López; et al. (Histochemistry and Cell Biology, 2025)

Lightweight artificial aggregates from ornamental rock cutting sludge and aggregate washing sludge: raw material for sustainable construction and agriculture - María Teresa Cotes-Palomino; Jacinto Alonso-Azcárate; Antonio Conde-Sánchez; Alejandro Dubbelman Vizcaíno; Ana B. López; Carmen Martínez-García; Ana M. Martínez-Rodríguez; Ana Cecilia Revelo Rodríguez; Francisco José Troyano Pérez; Carlos Javier Cobo-Ceacero (Environmental Research, 2025)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Effects of Schoenoplectus americanus (Pers.) Volkart Ex Schinz & R.Keller and Phragmites australis (Cav.) on the Water Quality Improvement of Moderately Saline Wastewater - Sarahi Josefina Estrada-Loredo; Rodolfo Cisneros-Almazán; Gerson Alonso Soto-Peña; Alejandro Hernández-Morales; María del Socorro Santos-Díaz (Wetlands, 2025)

Chemical composition of the harvested subtidal kelp, Lessonia trabeculata, from a coastal location in central Chile - Camila Gonzalez-Alonso-de-Linaje; Pippa Moore; Dan Smale; Louise Delion; Catalina S. Ruz; Rodrigo Muñoz-Cordovez; Praxedes Muñoz; Fadia Tala; Roberto A. Uribe; Alejandro Pérez-Matus (Algal Research, 2025)

Development of oxygen scavenging packaging with trans-polyoctenamer rubber to enhance the shelf life of walnuts - Gracia López-Carballo; Pedro Vázquez; Florian Schwager; Alejandro Aragón-Gutierrez; Jose M. Alonso; Carol López-de-Dicastillo; Pilar Hernández-Muñoz; Rafael Gavara (Food Packaging and Shelf Life, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

A soundscape approach for a short-term acoustic monitoring of a critically endangered Cuban frog - Mariam Curbelo Cruz; Sergio L. del Castillo Domínguez; Leandro Galano Machado; Alejandro Herrera Rodeiro; Carlos A. Mancina; Roberto Alonso Bosch (Biodiversity and Conservation, 2025)

Wind sea and swell discrimination in the outer Rio De La Plata Estuary, South Atlantic Ocean - Alejandro Salimbeni; Guadalupe Alonso; Alexander Babanin; Walter Dragani (Regional Studies in Marine Science, 2025)

Recharge area estimation by block and mountain front for the Los Humeros Geothermal Field, Puebla, Mexico: Advancing the conceptual model - Thomas Gunter Kretzschmar; José Alonso Aguilar-Ojeda; Enrique Iñiguez; Jorge Alejandro Ávila-Olivera; Julio César Cañas-Ramírez; Brenda Estela García-Sánchez; Gabriela Michel Vara-Castro (Journal of South American Earth Sciences, 2025)

Surfactant protein SP-B: one ring to rule the molecular and biophysical mechanisms of the pulmonary surfactant system - Alejandro Alonso; Bárbara Olmeda; Jesús Pérez-Gil (Biophysical Reviews, 2025)

Net primary productivity but not its remote‐sensing proxies predict mammal diversity in Andean‐Amazonian rainforests - Kim L. Holzmann; Pedro Alonso‐Alonso; Yenny Correa‐Carmona; Andrea Pinos; Felipe Yon; Alejandro Lopera; Gunnar Brehm; Alexander Keller; Ingolf Steffan‐Dewenter; Marcell K. Peters (Ecology, 2025)
Tropical forests are disappearing, but we have a limited understanding of the factors driving species coexistence in mammal communities of old‐growth forest ecosystems. The total energy that is bound by plants is assumed to be a key factor determining mammalian species richness, but accurately measuring energy flows in complex ecosystems is difficult, and most studies therefore rely on remote‐sensing‐based surrogates of net primary productivity (NPP). We monitored mammal species richness across three seasons using camera traps on 26 study plots along a forested, elevational gradient from 245 to 3588 m above sea level in southeastern Peru for which a unique dataset on field‐measured NPP exists. Using linear‐regression models and path analysis, we disentangled the effects of climate and NPP on the diversity of mammals, testing the predictions of the more‐individuals hypothesis, stating that energy availability drives the number of individuals and, thus, the number of coexisting species. We compared detailed field measurements of NPP with remote‐sensing products (MODIS NPP and MODIS NDVI). Mammal species richness, abundance, and biomass decreased in a negative exponential pattern with elevation. Field‐measured data on NPP, which was largely driven by temperature, was a strong predictor of both abundance and species richness, while remotely sensed proxies for NPP failed to accurately predict mammal diversity. Our study underpins the importance of field‐based ecosystem data and emphasizes the role of high primary productivity for maintaining diverse mammal communities, which is a particularly pressing issue in light of recent anthropogenic impacts on the Amazonian forest system.

Enhanced Cyanide Oxidation to Cyanate via Photocatalytic Ozonation: Comparing Sol–Gel and Hydrothermal Synthesis of BiVO4 Catalysts - Johan A. Vargas-Rueda; Alejandro R. Alonso; Rosa M. Luna-Sánchez; L. Lartundo-Rojas; Román Cabrera-Sierra (Water, Air, & Soil Pollution, 2024)
Bismuth vanadate has been reported as a promising active semiconductor for visible light harvesting. However, the rapid recombination of charge carriers has limited its photocatalytic properties. As an alternative route to treat contaminated water containing cyanide ions, photoactivated BiVO 4 in combination with ozone has been investigated. BiVO 4 photocatalysts were synthesized by microwave-assisted hydrothermal method, as well as by sol–gel, obtaining the monoclinic crystalline structure and a band gap of ~ 2.5 eV by XRD and UV–Vis DRS. The morphological analysis, elemental chemical composition, BET surface area, stability, and photoluminescence characteristics were carried out for both samples. Although the majority composition belongs to BiVO 4 , the presence of secondary phases was confirmed by XPS. The BiVO 4 obtained by sol–gel (sol–gel BVO) exhibited superior photocatalytic performance with a lower reaction time (15 min) to oxidize free cyanide under visible-light radiation in combination with ozone. The degradation kinetics is described by pseudo-zero-order kinetics, and the rate constant (k 0 ) of BiVO 4 synthesized by microwave-assisted hydrothermal method was found to be the lower of the two. The high efficiency of the photocatalytic ozonation for the removal of free cyanide can be ascribed to a combination of two oxidation systems and the synergy of both processes.

Barriers and enablers of life cycle assessment in small and medium enterprises: a systematic review - Rodrigo Gómez-Garza; Leonor Patricia Güereca; Alejandro Padilla-Rivera; Alonso Aguilar Ibarra (Environment, Development and Sustainability, 2024)
Businesses are facing increasing pressure from multiple stakeholders to integrate sustainability into their practices and business models. Although Small and Medium-sized Enterprises (SMEs) represent at least 90% of businesses worldwide and contribute approximately 60% of environmental impacts, assessing and improving their sustainability performance is not a priority for them. SMEs can address sustainability issues through the application of the different Life Cycle Assessment (LCA) approaches. LCA focuses solely on the environment; however, other forms, such as social, costing, sustainability, and organizational LCA, enable practitioners to assess impacts across the entire life cycle of the studied system, each with different scopes and approaches. However, LCA remains in the domain of large companies. This article aims to identify the main barriers and enablers of LCA in SMEs for wider use as a tool to improve sustainability performance. Through a systematic review of the scientific literature on LCA among SMEs applying the Standardized Technique for Assessing and Reporting Reviews of LCA data, a sample of 61 articles provides a 20-year history. Our results characterize the application of LCA in SMEs through six main aspects. Our main conclusions identify three main barriers to the application of LCA among SMEs: lack of trained personnel, lack of data, and high costs. To overcome these barriers, we found that narrowing down the scope using simplified methods in clusters can increase the use of LCA among SMEs. A simplified SME cluster-elaborated LCA can be used to qualitatively identify sustainability hotspots, develop suitable strategies to improve sustainability performance, and respond to market requests.

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Evaluation of homogeneous and heterogeneous catalytic strategies for furfural production from sugar-derived biomass in a solvent-free green pressurized reaction media (subcritical water-CO2) - Alba E. Illera; Helena Candela; Alejandro Bermejo-López; Pedro Barea; Patricia Alonso-Riaño; Óscar Benito-Román; Sagrario Beltrán; M. Teresa Sanz (Biomass and Bioenergy, 2024)

Genome wide association mapping of end-use gluten properties in bread wheat landraces (Triticum aestivum L.) - Matilde López-Fernández; Alejandro Chozas; Elena Benavente; Elia Alonso-Rueda; Julio Isidro y Sánchez; Laura Pascual; Patricia Giraldo (Journal of Cereal Science, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates - Fernanda Alves‐Martins; Juliana Stropp; Leandro Juen; Richard J. Ladle; Jorge M. Lobo; Javier Martinez‐Arribas; Paulo De Marco Júnior; Leandro Schlemmer Brasil; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Alex Córdoba‐Aguilar; Emmy Fiorella Medina‐Espinoza; et al. (Journal of Biogeography, 2024)
Aim Insects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completeness on climate–richness relationships using a comprehensive database of odonates. Location The Neotropics. Taxon Odonata. Methods Using 56,535 records collected from 1970 to 2021, we assess whether climate–species richness models vary under different scenarios of survey completeness. Results Our survey compilation revealed that most Neotropical diversity of Odonata likely remains unknown. Only 1% of the one‐degree cells covering the Neotropics held reliable information on odonate species richness, with particularly severe gaps in the Caribbean, Central America, northeastern Brazil and northern Chile. Temperature, precipitation and potential evapotranspiration exert consistent effects on Odonata richness across the entire Neotropics, regardless the level of survey completeness. Whereas seasonality‐related variables are less important predictors of species richness at the biogeographical scale. Main Conclusions By highlighting areas where inventories are more reliable and identifying regions that require increased data collection efforts and mobilization, our assessment offers a roadmap for improving the reliability of odonate inventories in the Neotropics. Furthermore, our findings underscore the importance of accounting for varying levels of survey completeness in macroecological models to reveal robust climate–species richness relationships. Simultaneously, they highlight strong climatic predictors of species richness, irrespective of survey effort intensity. These predictors provide a solid foundation for modelling and predicting odonate species richness in the Neotropics.

Ocean waves in the southwestern Atlantic Ocean: An evaluation of global wave models - Alejandro Salimbeni; Walter Dragani; Guadalupe Alonso (International Journal of Climatology, 2024)
In situ wave observations are essential for implementing coastal management strategies, designing coastal and offshore structures and understanding many processes related to sedimentology and marine biology. Despite their importance, these observations are rather scarce in the coastal areas of southeastern South America. Moreover, the existing observations are discontinuous, with several gaps and no simultaneity. Today, global wave models have improved their performance by providing reliable wave parameters with high resolution and coverage even at near‐shore areas. In this work, wave parameters from five global models were compared with significant wave heights ( H S ), peak periods ( T ) and propagation direction at nine sites located at the Southwestern South Atlantic Ocean. The global products used were WAVERYS (Global Reanalysis Wav 001 032), IOWAGA (WAVEWATCH III Hindcast – WW3 – Global grid – CFSR), ERA5 (ECMWF reanalysis), NOAA WW3 – 30‐year Hindcast Phase 2 and NCEP/EMC Operational global wave model GFS – Wave. Mean arithmetic error (Bias), root mean square deviation, scatter index and the Pearson linear correlation coefficient ( r ) were assessed at each location where wave observations were available. The best agreements for H S were obtained at the deepest sites located farther from the coast. Lower statistical metrics were achieved at coastal sites where the bathymetry is roughly represented by the global models. The calculated correlation coefficients were found to be lower for T than for H S . Overall, T was slightly underestimated by global models. Wave propagation directions were excellently represented by global models at offshore sites. The WAVERYS model is the global product that best represents the wave parameters in the study area, probably due to its higher spatial resolution (0.2°) and more realistic atmospheric forcing (ERA5). In addition, it satisfactorily represents the temporal variability of H S in open water as well as swell characteristics at the outer the Río de la Plata.

Differential effects of coverslip-induced hypoxia and cobalt chloride mimetic hypoxia on cellular stress, metabolism, and nuclear structure - Florencia Lamela; Ronell Bologna-Molina; Felipe Parietti; Vanesa Pereira-Prado; Magdalena Millán; Alejandro Silva; Juan Llaguno; Julia Alonso; Ariel Fernández; José Sotelo-Silveira; Manoela Domingues; Miguel Arocena; et al. (Tissue and Cell, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Pancreatic adenocarcinoma treated with surgical resection, toceranib phosphate and firocoxib in a dog: a case report - Manuel Fuertes-Recuero; Esther Vázquez-Fernández; Guillermo Lizasoain-Sánz; Amanda Arroba-Alonso; Alejandro Sánchez-López; Elena Martínez-de-Merlo; María Suárez-Redondo; Gustavo Ortiz-Diez (Veterinary Research Communications, 2024)
Exocrine pancreatic carcinomas are rarely reported in dogs. A ductal pancreatic adenocarcinoma in a 10-year-old intact beagle is described in this report. The diagnosis was made based on clinical signs, imaging (abdominal ultrasound and CT scan) and histopathology. Treatment consisted of partial right lobe pancreatectomy followed by adjuvant therapy with toceranib phosphate (Palladia®) and firocoxib (Previcox®) for six months. The treatment was well tolerated, and the survival time was 445 days. To our knowledge, this is the longest survival reported in the literature for a dog diagnosed with exocrine pancreatic adenocarcinoma. The results described here may contribute to provide a better understanding about this neoplasia and potential treatment options.

Integrated coastal zone management in Colombia: 25 years of implementing an environmental planning policy - Paula Cristina Sierra-Correa; Ángela Cecilia López Rodríguez; David Alejandro Alonso Carvajal; Francisco Armando Arias Isaza (Marine Policy, 2024)

Chemical and C and N stable isotope compositions of three species of epiphytic Tillandsia in a Caribbean coastal zone: air pollution sources and biomonitoring implications - Yasser Morera-Gómez; Alejandro Armas-Camejo; Jesús Miguel Santamaría; Carlos Manuel Alonso-Hernández; Esther Lasheras; David Widory; David Elustondo (Isotopes in Environmental and Health Studies, 2024)

Metasomatized mantle under the Eastern Mexican Alkaline Province: evidence from the Oligocene Rincón Murillo Gabbro, Sierra de San Carlos-Cruillas, NE México - Victor Alejandro Leal-Cuellar; Juan Alonso Ramírez-Fernández; Reneé González-Guzmán; Fernando Velasco-Tapia; Luigi Solari; Luis Alejandro Elizondo-Pacheco; Juan Carlos Montalvo-Arrieta; José Jovany Rivera-García; Bodo Weber (International Geology Review, 2024)

Efficacy of a mirid predator and an eulophid parasitoid to the tomato potato psyllid Bactericera cockerelli control on pepper plants - Alejandro O. Guzmán-Pedraza; Ana Mabel Martínez; Ángel Rebollar-Alviter; Luis J. Palma-Castillo; Sinue I. Morales-Alonso; Juan M. Chavarrieta-Yáñez; José I. Figueroa; Samuel Pineda (BioControl, 2024)

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Oral sugar and vasopressin: Possible alternative in the management of ovine pregnancy toxemia - José-Ramiro González-Montaña; María-José Martín-Alonso; Luis G. Cal-Pereyra; Alejandro Benech; Francisco Escalera-Valente; Ángel J. Alonso-Diez (Small Ruminant Research, 2023)

Repeated asynchronous evolution of single‐species endemics of ivies ( Hedera L.) in Macaronesian archipelagos - Angélica Gallego‐Narbón; Alejandro Alonso; Virginia Valcárcel; Mario Fernández‐Mazuecos (Journal of Biogeography, 2023)
Aim Evolutionary studies of oceanic island endemics are usually focused on lineages that have experienced in situ radiation, while those that speciated once on the island or archipelago but have not further diversified (single‐species endemics) remain understudied. The Macaronesian archipelagos, in the Atlantic Ocean, are home to significant numbers of single‐species endemics. The genus Hedera L. (12 species) includes three single‐species endemics from three Macaronesian archipelagos with putatively independent origins. Here, we tested the role of phylogenetic niche conservatism in their evolution. To that end, we (1) reconstructed the spatio‐temporal origin of Macaronesian ivies using phylogenomics, and (2) assessed the role of climatic niche during their colonization and speciation. Location Azores, Canary Islands, Madeira, western Mediterranean. Taxon Hedera spp. Methods We used 166 samples representing all Hedera species to generate genotyping‐by‐sequencing (GBS) libraries and performed time‐calibrated phylogenomic and biogeographic analyses. Climatic preferences and climatic niche evolution were assessed using a geo‐referenced database of the western ivy species (2,297 records). Results Independent and asynchronous colonization and speciation were estimated for the three Macaronesian ivies, resulting in different degrees of phylogenetic and climatic niche differentiation: H. canariensis displayed an early divergence (7.5–12 Ma) and high phylogenetic and niche isolation; H. azorica had intermediate phylogenetic isolation and niche divergence from its closest relative H. helix (4.4–6.8 Ma) and H. maderensis was embedded within the climatically similar H. iberica (2.8–4.6 Ma) . A strong phylogenetic signal was suggested for climatic niche in the western clade of Hedera , where the three Macaronesian ivies are placed. Main Conclusions The three Macaronesian ivies represent the evolutionary stages leading to the emergence of single‐species island endemics. Climatic niche conservatism appears to be involved in the evolution of single‐species endemics, first by facilitating island colonization, and then by limiting in situ diversification.

Constraints on the origin of the cenozoic intraplate aldama volcanic field, tamaulipas, NE México - José Jovany Rivera-García; Juan Alonso Ramírez-Fernández; Fernando Velasco-Tapia; Jorge Alán Salinas-Jasso; María Teresa Orozco-Esquivel; Daniel Stockli; Víctor Alejandro Leal-Cuellar; Luis Alejandro Elizondo-Pacheco (Journal of South American Earth Sciences, 2023)

Body mass decline in a M editerranean community of solitary bees supports the size shrinking effect of climatic warming - Carlos M. Herrera; Alejandro Núñez; Javier Valverde; Conchita Alonso (Ecology, 2023)
The long‐known, widely documented inverse relationship between body size and environmental temperature (“temperature‐size rule”) has recently led to predictions of body size decline following current climatic warming (“size shrinking effect”). For keystone pollinators such as wild bees, body shrinking in response to warming can have significant effects on pollination processes but there is still little direct evidence of the phenomenon because adequate tests require controlling for confounding factors linked to climate change (e.g., habitat change). This paper assesses the shrinking effect in a community of solitary bees from well‐preserved habitats in the core of a large nature reserve experiencing climatic warming without disturbances or habitat changes. Long‐term variation in mean body mass was evaluated using data from 1704 individual bees (137 species, 27 genera, 6 families) sampled over 1990–2023. Climate warmed at a fast rate during this period, annual mean of daily maximum temperature increasing 0.069°C/year on average during 2000–2020. Changes in bee body mass verified expectations from the size shrinking effect. The mean individual body mass of the community of solitary bees declined significantly, irrespective of whether the analysis referred to the full species sample or only to the subset of species that were sampled in both the old (1990–1997) and recent (2022–2023) periods. On average, body mass declined ~0.7%·year −1 , or an estimated average cumulative reduction of ~20 mg per individual bee from 1990 to 2023. Proportional size reduction was greatest among large‐bodied species, ranging from around −0.6%·year −1 for the smallest species to −0.9%·year −1 for the largest ones. Declining rate was steeper for cavity‐nesting than ground‐nesting species. The pollination and mating systems of bee‐pollinated plants in the study region are probably undergoing significant alterations as a consequence of supra‐annual decline in bee body mass.

A protocol for lixiviation of micronized plastics for aquatic toxicity testing - Rodrigo Almeda; Kuddithamby Gunaalan; Olalla Alonso-López; Alejandro Vilas; Christelle Clérandeau; Tara Loisel; Torkel Gissel Nielsen; Jérôme Cachot; Ricardo Beiras (Chemosphere, 2023)

5'/3' RACE method for sequencing the 5' and 3' untranslated regions of Zika virus - Diego Alejandro Álvarez-Díaz; José Aldemar Usme-Ciro; Sheryll Corchuelo; Julián Ricardo Naizaque; Jorge Alonso Rivera; Hernán Darío Castiblanco-Martínez; Orlando Torres-Fernández; Aura Caterine Rengifo (Archives of Virology, 2023)

Late stages of megagametophytogenesis: Archegonial development in Zamiaceae - M. Ydelia Sánchez-Tinoco; Dennis Wm. Stevenson; Andrew P. Vovides; Alejandro Alonso López; Lourdes G. Iglesias-Andreu; Edmundo García Moya; Galdy Hernández-Zárate (Flora, 2023)

Ensuring a just energy transition: A distributional analysis of diesel tax reform in Spain with stakeholder engagement - Manuel Tomás; Xaquín García-Muros; Eva Alonso-Epelde; Iñaki Arto; Alejandro Rodríguez-Zúñiga; Cristina Monge; Mikel González-Eguino (Energy Policy, 2023)

Geologic framework of Cretaceous plutons along a west-to-east transect in the southern Peninsular Ranges batholith, Baja California, Mexico: Insights from geochemical, isotopic, and geochronologic data - Xochitl Guadalupe Torres-Carrillo; Luis Alberto Delgado-Argote; Bodo Weber; Manuel Contreras-López; Tomás Alejandro Peña-Alonso; Porfirio Avilez-Serrano; Doris Karina Gómez-Álvarez (International Geology Review, 2023)

Detection and genetic characterization of feline retroviruses in domestic cats with different clinical signs and hematological alterations - Gabriel Eduardo Acevedo-Jiménez; Rosa Elena Sarmiento-Silva; Rogelio Alejandro Alonso-Morales; Rodolfo Córdova-Ponce; Hugo Ramírez-Álvarez (Archives of Virology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Evaluation of simple laboratory parameters in SARS-CoV-2 infection: the role of ratios - Crhistian-Mario Oblitas; Francisco Galeano-Valle; Carmen Cuenca-Carvajal; Sandra Piqueras-Ruiz; Rubén Alonso-Beato; Álvaro Alejandre-de-Oña; Paula Carrascosa-Fernández; Agustín-Diego Chacón Moreno; Alejandro Parra-Virto; María-Teresa Pérez Sanz; Laura Abarca Casas; Clara Millán-Nohales; et al. (Infectious Diseases, 2022)

Engytatus varians as agent for dispersal of Spodoptera exigua nucleopolyhedrovirus - Ana Mabel Martínez; Samara Zamudio-López; Alejandro Oxalis Guzmán-Pedraza; Sinue Isabel Morales-Alonso; Javier Valle; Selene Ramos-Ortiz; Norma Zamora-Avilés; José Isaac Figueroa; Samuel Pineda (Journal of Pest Science, 2022)

Inter-laboratory validation of an ISO test method for measuring enzyme activities in soil samples using colorimetric substrates - Nathalie Cheviron; Virginie Grondin; Christelle Marrauld; Françoise Poiroux; Isabelle Bertrand; Josiane Abadie; Pascal Pandard; Wassila Riah-Anglet; Caroline Dubois; Stanislav Malý; Catarina R. Marques; Inmaculada Valverde Asenjo; et al. (Environmental Science and Pollution Research, 2022)

Coastal habitat evidences and biological data of Alepisaurus ferox (Aulopiform; Alepisauridae) from northwestern Iberian Peninsula - Rafael Bañón; Álvaro Roura; Cristina García-Fernández; Alexandre Alonso-Fernández; Alejandro de Carlos (Marine Biodiversity, 2022)

Green and Golden Obsidian of “Cerro de Las Navajas”, Hidalgo (Mexico): Geoarchaeological Heritage That Deserves International Recognition - Miguel A. Cruz-Pérez; Carles Canet; Alejandro Pastrana; Silvia Domínguez-Peláez; Lucero Morelos-Rodríguez; Luis Carcavilla; Erika Salgado-Martínez; Peter Krieger; Eduardo J. García-Alonso; Raymundo G. Martínez-Serrano; Sara I. Franco; Telma G. Castro-Romero; et al. (Geoheritage, 2021)

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

Early Mississippian precollisional, peri-Gondwanan volcanic arc in NE-Mexico: Aserradero Rhyolite from Ciudad Victoria, Tamaulipas - Juan Alonso Ramírez-Fernández; Eduardo Alejandro Alemán-Gallardo; Denisse Cruz-Castillo; Fernando Velasco-Tapia; Uwe Jenchen; Raúl Becchio; Lorena De León-Barragán; Juan Moisés Casas-Peña (International Journal of Earth Sciences, 2021)

Bacitracin is a non-competitive inhibitor of porcine M1 family neutral and glutamyl aminopeptidases - Yarini Arrebola; Laura Rivera; Alejandro Pedroso; Rory McGuire; Mario E. Valdes Tresanco; Gretchen Bergado; Jean-Louis Charli; Belinda Sánchez; Isel Pascual Alonso (Natural Product Research, 2021)

Gas Exchange Parameters, Fruit Yield, Quality, and Nutrient Status in Tomato Are Stimulated by ZnO Nanoparticles of Modified Surface and Morphology and Their Application Form - Eneida Adilene Pérez-Velasco; Luis Alonso Valdez-Aguilar; Rebeca Betancourt-Galindo; Javier Martínez-Juárez; Samuel Alejandro Lozano-Morales; José Antonio González-Fuentes (Journal of Soil Science and Plant Nutrition, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Landscape factors modulating patterns of salmonid distribution during summer in north Patagonian rivers - Mailén E. Lallement; Magalí Rechencq; María V. Fernández; Eduardo Zattara; Alejandro Sosnovsky; Pablo Vigliano; Gilda Garibotti; Marcelo F. Alonso; Gustavo Lippolt; Patricio J. Macchi (Journal of Fish Biology, 2020)
Understanding how ecosystem processes influencing fish distribution operate across spatial scales is important to understand biological invasions. Salmonids, originally from the Northern Hemisphere, have been repeatedly introduced throughout the world, making them an ideal group to test hypotheses about factors driving invasions. We assessed the influence of environmental variables at the watershed scale on the abundance and structure of salmonid assemblages in the breeding streams of the Upper Limay river basin, Rio Negro, Argentina. We combined field captures with digital map data and geographic information systems to examine landscape‐level patterns of salmonid abundance in 35 representative sub‐basins of the environmental gradient. We employed a hierarchical cluster analysis and classification and regression tree models to relate the abundance of salmonids and types of species assemblages with environmental characteristics at watershed level. We found stream localization, precipitation regime, altitude and air temperature to be important predictors of the abundance and assemblage structure of salmonids. Total catches showed an increasing gradient of catch‐per‐unit‐effort from west to east and from north to south, with Oncorhynchus mykiss being the most abundant species. O. mykiss relative abundance was westward skewed, where smaller catchments with steeper and shaded valleys are drained by less productive streams with more irregular hydrological regimes, like those found in this species' North American native range. In contrast, the abundance of Salmo trutta abundance was eastward skewed, where larger, sunnier and more gently sloped catchments result in more productive streams with stable hydrological regimes, like those found in that species' European native range. Thus, differential salmonid abundance could result from the interplay between the evolutionary fingerprint left by each species' native environment (especially flow and temperature regimes) and the availability of those conditions in new environments to which they have been translocated. By furthering our understanding of how landscape conditioned invasion success, these findings can help guide the management of economically important introduced fish.

Life-long testosterone and antiandrogen treatments affect the survival and reproduction of captive male red-legged partridges (Alectoris rufa) - Carlos Alonso-Alvarez; Alejandro Cantarero; Ana Ángela Romero-Haro; Olivier Chastel; Lorenzo Pérez-Rodríguez (Behavioral Ecology and Sociobiology, 2020)
Sexual steroids can play an important role as life-history organizers. In males, high circulating testosterone levels induce physiological/behavioral costs and benefits, leading to trade-offs. However, studies simultaneously testing the impact of these levels in both fitness components (survival and fecundity) during lifetime are scarce and limited to wild birds. To determine the mortality causes or hormonal manipulation impacts on male fertility is, nonetheless, a difficult task in free-ranging animals that could be easier in captivity. We longitudinally monitored captive red-legged partridges ( Alectoris rufa ) and exposed males to high exogenous testosterone levels, anti-androgens, or a control treatment during each breeding period throughout their lives. Theory predicts that individuals maintaining high androgen levels should obtain higher fitness returns via reproduction, but suffer reduced longevity. Testosterone-treated male partridges, accordingly, lived shorter compared to controls, since they were more prone to die from a natural bacterial infection. However, the same birds seemed to have a lower capacity to fertilize eggs, probably due to endocrine feedback reducing testicular mass. These results show that exogenous testosterone can exert unpredicted effects on fitness parameters. Therefore, caution must be taken when drawing conclusions from non-fully controlled experiments in the wild. Males treated with the androgen-receptor blocker flutamide did not outlive controls as predicted by the life-history trade-off theory, but their mates laid eggs with higher hatching success. The latter could be due to mechanisms improving sperm quality/quantity or influencing maternal investment in egg quality. Testosterone receptor activity/amount could thus be as relevant to fitness as testosterone levels. Significance statement It has repeatedly been hypothesized that high testosterone levels induce a cost in terms of reduced lifetime reproductive success. This can be due to reduced fecundity or via shorter lifespan. This is, however, only supported by a handful of studies, mostly in wild birds. We tested this in captive male red-legged partridges, which allowed us to determine reproductive success and mortality causes. We increased testosterone levels or blocked its action with antiandrogens throughout life. High testosterone levels reduced the survival by making birds more prone to die by infection. The eggs produced by their mates also showed lower hatching success, a probable manipulation artifact that should be considered in avian studies in the wild. Interestingly, the androgen-receptor blocker flutamide increased lifetime hatching success compared to controls, suggesting that androgen receptor amounts/activity are even more relevant to fitness than testosterone levels.

Cardioembolic Ischemic Stroke Gene Expression Fingerprint in Blood: a Systematic Review and Verification Analysis - Teresa García-Berrocoso; Elena Palà; Marta Consegal; Benedetta Piccardi; Alex Negro; Natalia Gill; Anna Penalba; Hector Huerga Encabo; Israel Fernández-Cadenas; Andreas Meisel; Christian Meisel; Glen C. Jickling; et al. (Translational Stroke Research, 2020)

Baseline for plastic and hydrocarbon pollution of rivers, reefs, and sediment on beaches in Veracruz State, México, and a proposal for bioremediation - Leticia Narciso-Ortiz; Alejandro Coreño-Alonso; Diana Mendoza-Olivares; Carlos Alexander Lucho-Constantino; Manuel Alejandro Lizardi-Jiménez (Environmental Science and Pollution Research, 2020)

Apparently contradictory routes in the expansion of two fish species in the Eastern Atlantic - Rafael Bañón; Alejandro de Carlos; Alexandre Alonso‐Fernández; Fernando Ramos; Francisco Baldó (Journal of Fish Biology, 2020)
One specimen of the boreal Clupea harengus (Clupeidae) was caught southerly, in the Gulf of Cádiz (southern Spain), whereas a specimen of the subtropical Epinephelus aeneus (Serranidae) was caught northerly, in Galician waters (north‐west of Spain). These catches represent a new southernmost record in the eastern Atlantic for C. harengus and the second northernmost for E. aeneus . The co‐occurrence of warm and cold affinity fishes in temperate latitudes is unusual, but the existence of anomalies in the temperature of the Atlantic waters could be behind these findings.

An approach to quantitative plant–soil relationships of saltcedar woodlands throughout central and southeastern Iberian Peninsula (Spain) - Joaquín Moreno; Alejandro Terrones; María Ángeles Alonso; Ana Juan (European Journal of Forest Research, 2019)

Evidence for an Ordovician continental arc in the pre-Mesozoic basement of the Huizachal–Peregrina Anticlinorium, Sierra Madre Oriental, Mexico: Peregrina Tonalite - Eduardo Alejandro Alemán-Gallardo; Juan Alonso Ramírez-Fernández; Augusto Antonio Rodríguez-Díaz; Fernando Velasco-Tapia; Uwe Jenchen; Esther María Cruz-Gámez; Lorena De León-Barragán; Ignacio Navarro-De León (Mineralogy and Petrology, 2019)

Unusual occurrences of fishes along the Northeast Atlantic: new biological and distributional data - RAFAEL BAÑÓN; RAQUEL TEJERINA; XESÚS MORALES; ALEXANDRE ALONSO-FERNÁNDEZ; DAVID BARROS-GARCÍA; ALEJANDRO DE CARLOS (Mediterranean Marine Science, 2019)
The occurrences of 13 specimens belonging to 9 species of little known marine fishes in the Northeast Atlantic in 2017 and 2018 are reported. Information about the morphology and new findings of Decapterus tabl and Decapterus macarellus (Carangidae), Kyphosus vaigiensis (Kyphosidae), Remora osteochir (Echeneidae), Antigonia capros (Caproidae), Hyperoglyphe perciformis (Centrolophidae), Halobatrachus didactylus (Batrachoididae), Parapristipoma octolineatum (Haemulidae) and Zu cristatus (Trachypteridae) are reported in different locations, where they are categorized as unusual or rare. Morphometric and meristic parameters confirm the identification to species level of each specimen, also supported by DNA barcoding. Histological examination of reproductive tissue is carried out in four specimens to know the sex and their reproductive stage. All species are known from other areas of the Atlantic Ocean, but these findings are an important contribution to understanding their biology and distribution. These include a new northernmost record of Remora osteochir and Decapterus tabl in the eastern Atlantic and the first records of Antigonia capros, Hyperoglyphe perciformis, Halobatrachus didactylus and Parapristipoma octolineatum from Galician waters.

β-(1,4)-Galactan remodelling in Arabidopsis cell walls affects the xyloglucan structure during elongation - María Moneo-Sánchez; Alejandro Alonso-Chico; J. Paul Knox; Berta Dopico; Emilia Labrador; Ignacio Martín (Planta, 2019)

Unmanned aerial vehicle observations of water surface elevation and bathymetry in the cenotes and lagoons of the Yucatan Peninsula, Mexico - Filippo Bandini; Alejandro Lopez-Tamayo; Gonzalo Merediz-Alonso; Daniel Olesen; Jakob Jakobsen; Sheng Wang; Monica Garcia; Peter Bauer-Gottwein (Hydrogeology Journal, 2018)

Geographic range expansion of Ephippion guttifer (Tetraodontidae) in the north‐eastern Atlantic - Rafael Bañón; Alexandre Alonso‐Fernández; David Barros‐García; María‐Berta Rios; Alejandro de Carlos (Journal of Fish Biology, 2018)
The first record of the prickly puffer Ephippion guttifer (Tetraodontidae) from Galician waters (north‐west Spain) is reported based on a male specimen of 570 mm total length ( L T ) caught in the Ría de Vigo. Morphometric, meristic and DNA barcode data confirmed the identification. Histological examination of reproductive tissue was carried out in this species for the first time, showing a mature male in an actively spawning phase. A historical revision invalidates a previous record and establishes this as the northernmost confirmed capture ever reported in the north‐eastern Atlantic Ocean.

Halophytic plant community patterns in Mediterranean saltmarshes: shedding light on the connection between abiotic factors and the distribution of halophytes - Joaquín Moreno; Alejandro Terrones; Ana Juan; María Ángeles Alonso (Plant and Soil, 2018)

Structural and environmental effects on an assemblage of echinoderms associated with a coral community - Rosa Carmen Sotelo-Casas; Amílcar Leví Cupul-Magaña; Fabián Alejandro Rodríguez-Zaragoza; Francisco Alonso Solís-Marín; Alma Paola Rodríguez-Troncoso (Marine Biodiversity, 2018)

The fractal dimension of a conspicuous ornament varies with mating status and shows assortative mating in wild red-legged partridges (Alectoris rufa) - Alejandro Cantarero; Jesús Carrasco Naranjo; Fabián Casas; Francois Mougeot; Javier Viñuela; Carlos Alonso-Alvarez (The Science of Nature, 2018)

Study on the removal of hormones from domestic wastewaters with lab-scale constructed wetlands with different substrates and flow directions - José Alberto Herrera-Melián; Rayco Guedes-Alonso; Alejandro Borreguero-Fabelo; José Juan Santana-Rodríguez; Zoraida Sosa-Ferrera (Environmental Science and Pollution Research, 2018)

d-Cloprostenol enhances estrus synchronization in tropical hair sheep - Alejandro Alavez Ramírez; Victor Manuel Meza Villalvazo; Emmanuel Sosa Arredondo; Hugo Alonso Ramírez Ramírez; Héctor Magaña Sevilla (Tropical Animal Health and Production, 2018)

Nest-dwelling ectoparasites reduce antioxidant defences in females and nestlings of a passerine: a field experiment - Jimena López-Arrabé; Alejandro Cantarero; Lorenzo Pérez-Rodríguez; Antonio Palma; Carlos Alonso-Alvarez; Sonia González-Braojos; Juan Moreno (Oecologia, 2015)

Anorectal Manometry in Wistar Rats with Inexpensive Setup: A Physiological Description of the Mechanical Activity - Alejandro Barriga-Rivera; Juan Luis Vinuesa; Manuel Lopez-Alonso (Journal of Medical and Biological Engineering, 2015)

Apoptosis for prediction of radiotherapy late toxicity: lymphocyte subset sensitivity and potential effect of TP53 Arg72Pro polymorphism - María J. Fuentes-Raspall; Isabel Caragol; Carmen Alonso; Teresa Ramón y Cajal; David Fisas; Alejandro Seoane; Nerea Carvajal; Sandra Bonache; Orland Díez; Sara Gutiérrez-Enríquez (Apoptosis, 2015)

A methodological improvement for assessing petrochemical projects through life cycle assessment and eco-costs - Miguel Angel Morales Mora; Elena Rosa Dominguez; Alonso Aguilar Ibarra; Nydia Suppen Reynaga; Sergio Alejandro Martínez Delgadillo (The International Journal of Life Cycle Assessment, 2014)

Expression of an HBcAg-based antigen carrying angiotensin II in Chlamydomonas reinhardtii as a candidate hypertension vaccine - Ruth E. Soria-Guerra; Jocelín I. Ramírez-Alonso; Alejandro Ibáñez-Salazar; Dania O. Govea-Alonso; Luz M. T. Paz-Maldonado; Bernardo Bañuelos-Hernández; Schuyler S. Korban; Sergio Rosales-Mendoza (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Taxonomic status of Ononis tridentata (Fabaceae) from Morocco, resolved by multivariate morphometric analyses - Jonás C. Agulló; Ana Juan; MÁngeles Alonso; Alejandro Terrones; Manuel B. Crespo (Plant Biosystems, 2013)

Sugar as nutritional supplement for the zoophytophagous predator Nesidiocoris tenuis - Pablo Urbaneja-Bernat; Miquel Alonso; Alejandro Tena; Karel Bolckmans; Alberto Urbaneja (BioControl, 2013)

Benefit of the integration of semantic 3D models in a fire-fighting VR simulator - Aitor Moreno; Álvaro Segura; Sisi Zlatanova; Jorge Posada; Alejandro García-Alonso (Applied Geomatics, 2012)

Genetic polymorphisms among C57BL/6 mouse inbred strains - Esther Zurita; Mónica Chagoyen; Marta Cantero; Rosario Alonso; Anna González-Neira; Alejandro López-Jiménez; José Antonio López-Moreno; Carlisle P. Landel; Javier Benítez; Florencio Pazos; Lluís Montoliu (Transgenic Research, 2011)

Hyaluronic Acid/Chitosan-g-Poly(ethylene glycol) Nanoparticles for Gene Therapy: An Application for pDNA and siRNA Delivery - Manuela Raviña; Eva Cubillo; David Olmeda; Ramón Novoa-Carballal; Eduardo Fernandez-Megia; Ricardo Riguera; Alejandro Sánchez; Amparo Cano; María José Alonso (Pharmaceutical Research, 2010)

Comparing bird assemblages in large and small fragments of the Atlantic Forest hotspots - Alejandro R. Giraudo; Silvia D. Matteucci; Julián Alonso; Justo Herrera; Raúl R. Abramson (Biodiversity and Conservation, 2008)

Long Term Variability in the Structure of Kelp Communities in Northern Chile and the 1997–98 ENSO - Julio A. Vásquez; J. M. Alonso Vega; Alejandro H. Buschmann (Journal of Applied Phycology, 2006)

Chitosan Nanoparticles as New Ocular Drug Delivery Systems: In Vitro Stability, in Vivo Fate, and Cellular Toxicity - Angela M. de Campos; Yolanda Diebold; Edison L. S. Carbalho; Alejandro Sánchez; María José Alonso (Pharmaceutical Research, 2005)

Chitosan Nanoparticles as New Ocular Drug Delivery Systems: in Vitro Stability, in Vivo Fate, and Cellular Toxicity - Angela M. de Campos; Yolanda Diebold; Edison L. S. Carvalho; Alejandro Sánchez; Maria José Alonso (Pharmaceutical Research, 2004)

Characterization of a naturally occurring new version of the cholesterol ester transfer protein (CETP) from small intestine - Ana L. Alonso; Alejandro Zentella-Dehesa; Jaime Mas-Oliva (Molecular and Cellular Biochemistry, 2003)